Avaliação da ação antifúngica em fungos de revestimento de uma solução fungicida e da prata coloidal - Moura Filho, José Nilson Bandeira de (Universidade Federal Rural do Semi-Árido, 2018)
Oftentimes, Civil construction suffers from factors that can not be controlled by men, including humidity, radiation, precipitation, as well as macro and microorganisms actions. Biodeterioration is characterized by a set of microorganism actions that act on the materials of the civil construction in a negative way, being able to alter the properties of these materials the same. It can range from an aesthetic deterioration with the presence of dark or yellowish spots or by the development of biofilm. Or, a more aggressive deterioration, altering the composition of the materials and degrading them. To solve this problem, the industry has been using some dry biocides, which have high efficiency in the fungicide action. However, some of them have a high leaching and can be harmful to human health. Thus, the study of alternative forms of biocides that have high efficiency and do not harm the environment nor the population has become more frequent. A laboratory solution made up of some chemical compounds was analyzed for fungicide action and the minimum concentration could inhibit fungal growth. Another alternative analyzed was colloidal water, synthesized by physical method, where silver ions were transferred to water that was used in varied concentrations aiming to analyze the effectiveness of the fungicide action. The action of the two compounds was evaluated by fungal growth in Petri dishes and the tests were performed in duplicate The fungicidal solution acted from a certain concentration and could affect the growth of colonies and inhibition of growth. Colloidal water failed to inhibit fungal growth, most likely by the low concentration of ions in the synthesized water.
Monografia
Keywords: Biodeterioração; Fungos; Biocidas; Solução fungicida; Íons de prata; Biodeterioration; Fungi; Biocides; Fungicide solution; Silver ions; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA